Evaluation of potato hybrids by the dynamics of accumulation of yield and starch content in tubers in agro-ecological conditions of the Volga-Vyatka region - N. F. Sintsova; I. V. Lyskova; E. I. Kratyuk; V. M. Arkhipov (Аграрная наука Евро-Северо-Востока)
The article provides the results of studying the accessions of potato in the nursery of dynamic test for 2019-2021 in agro-ecological conditions of the Volga-Vyatka region (Kirov region) by the yield and starch content in tubers. The objects of the study were 10 hybrids bred by Falenki Breeding Station - branch of Federal Agricultural Research Center of the NorthEast named N. V. Rudnitsky (FARC North-East). Early variety Udacha (Russian Potato Research Centre), middle-early variety Nevsky (North-West Research Institute of Agriculture), mid-season variety Chaika (FARC North-East) were taken as standard. Promising potato hybrids of different maturity groups with high potential yield have been selected: early variety 172- 13 (24.1 t/ha), middle-early varieties 27-07 (22.7 t/ha), 179-10 (22.9 t/ha), 233-12 (24.0 t/ha), mid-season 232-12 (22.4 t/ha). By favorable agro-weather conditions (2019) the highest yield (more than 28.0 % t/ha) was developed by hybrids: early 172-13, middle-early 27-07 and 179-10, mid-season 580-13. In the unstable environment of 2020 and 2021 the following hybrids were noted: middle-early 233-12 (19.6 and 27.7 t/ha) and mid-season 232-12 (19.2 and 24.0 t/ha). In the group of middle-early varieties with high starch content (15 % and more) during the years of study there were selected the hybrids 27-07, 179-10, 72-13, 182-13. The maximum accumulation of starch (18-21 %) was noted in mid-season hybrid 580-13. Significantly high inter-seasonal correlations by yield on the 60th day from the planting have been established, that characterized all the varieties as the most stable. On the 80th day there were noted weak inter-seasonal correlations that proved the instability of this parameter during the years which differed in weather conditions (strong interaction “genotype-environment”, that is the yield of variety samples during this period depended on the effect of environment factors). High inter-seasonal correlations by the parameter “starch content” on the 80th day have been revealed. The varieties and hybrids by the time of complete ripeness preserved the stability by this indicator unlike early harvesting periods when they were more dependable on the fluctuations of environmental factors.